Age Effects on Old/New Recognition Memory Involving Abstract Figures and Non-words - Toth, Monika; Sambeth, Anke; Blokland, Arjan (Frontiers in Aging Neuroscience, 2022)
Age-related memory problems posit a growing concern in our society. This study investigated the impact of age and memory strength on recognition memory of pre-experimentally unfamiliar abstract figures and non-words. We applied a three-phase old/new recognition memory paradigm and manipulated memory strength as a function of the Levels of Processing (deep vs. shallow) and repetition. Older adults relative to the young showed impairment in the correct identification of new items. As indicated by the lower discriminability indexes, the older adults also had difficulties discriminating the strongly (drawn/semantically processed) and the weakly (studied) embedded abstract figures but not the non-words. Age-related differences in reaction times were only evident with the abstract figures. Finally, our results revealed that the recognition performance was equally affected by memory strength in both age groups. The current findings agree with previous research on age-related impairment in new item recognition, which can be attributed to misrecollection and decreased sensitivity to novelty in the older adults than the young. The detected age effects on the discriminability of the drawn and studied abstract figures agree with the age-related impairment in the perceptual encoding hypothesis and support the notion related to the need for environmental support to reduce age effects. The lack of age effects with the non-words indicates that age effects on discriminability are stimulus-dependent. The current results support the notion that recognition memory in aging is only impaired under certain conditions and depends on the stimuli used.